Intercultural communicative skills in the training of industrial engineers: a case-study on students' perceptions - Gaspar, Marcelo (2019)
In order to understand the intercultural awareness development of engineering students, which is necessary for them to fully function in globalized educational and professional work contexts, a dedicated project was carried-out with Industrial Engineering students in a Higher Education Portuguese Polytechnic Institute during three successive academic years in the framework of an adjunct CLIL pilot experiment. Students’ perceptions were collected and assessed in order to tackle two main research questions: “Do students feel they have more opportunities for global employment or globally networked collaborative innovation?” and “What were the difficulties experienced because of the CLIL methodological approach?”. Preliminary findings point out that even though students feel that competence in English is important (or very important) concerning their work as engineers, the majority states not being proficient in that language. Students also refer that the CLIL approach allowed them to develop collaborative work with other colleagues and helped them understand better their own personal language learning needs, thus contributing to facilitate their communication in a foreign language.